Advancement Of Health Technology Methodologies: A Comprehensive Analysis Focused On Medical Devices - Yuqing, Dong; Binti Tajudin, Noraisyah; Nizamudin Inamdar, Mohammad (Cuestiones de Fisioterapia, 2023)
The main objective of the project is to discover how current medical technology might enhance healthcare delivery by facilitating the delivery of more focused, accurate, and efficient treatment. It is vital to integrate these technologies into operational and clinical processes for improved healthcare outcomes overall. The reason for this is the continued fast advancement of medical technology in the next years. This study extensively examines a wide range of medical equipment, including tools used for diagnosis, monitoring, and treatment. In order to analyse the influence of various medical equipment kinds on the development and improvement of health technology practices, this study aims to investigate the repercussions of varied effects created by these practices. Consider the technology's practicality, user-friendliness, data integration capabilities, and the positive impact it has on patient care and clinical decision-making. In order to determine the worth of medical gadgets, this research will examine their efficiency in streamlining operations, their frequency in reducing medical errors, and their accuracy in prescribing treatments. Methods from quantitative research have been used for this purpose. To achieve this goal, the researcher integrated qualitative and quantitative methods into our research. They recommend improving interoperability, undertaking real-time monitoring, and delivering tailored treatment, and they emphasise the strategic use of medical devices as a big step forward in the growth of health technology approaches.